ONTOLOGI, EPISTIMOLOGI, AKSIOLOGI, DAN AKTUALISASINYA PADA STUDI ISLAM (TAFSIR) - Setiawan, Iwan (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
This study aims to explain the concepts of ontology, epistemology, axiology, and their actualization in Islamic studies, especially in the study of interpretation. The focus is to understand the nature, sources, benefits, and objectives of Islamic education through a philosophical perspective. This study uses a qualitative approach with a type of library research. Data were obtained from various primary and secondary sources, including books, journals, and related articles. The data analysis technique used is qualitative analysis, with the process of collecting, processing, and reviewing relevant literature. The results of the study show that ontology, namely Islamic studies, includes the nature of human existence, nature, and God based on Islamic norms. Epistemology, namely knowledge in Islam comes from the senses, reason, intuition, inspiration, and revelation, with an emphasis on the harmonization of rationality and revelation. Axiology, namely Islamic studies aim to integrate Islamic values in human life, creating individuals who are devout and do good deeds. Actualization, namely philosophical thinking is applied in the reinterpretation of Islamic teachings to be in line with the development of science and technology, allowing for practical implementation in society. This study emphasizes the importance of Islamic philosophy as a framework for understanding Islamic education comprehensively and relevant to contemporary challenges.